Isotherm and Kinetics of Fe(II) Adsorption onto Chitosan in a Batch Process - Hamideh Radnia; Ali Asghar Ghoreyshi; Habibollah Younesi (Iranica Journal of Energy and Environment, 2011)
In this study removal of Fe(II) by chitosan adsorbent was experimentally investigated in a batch system. The adsorbent dose and pH of the metal solution was fixed at 0.15 g and 4, respectively. Adsorption experiments were carried out at initial concentration range of 10–50 mg l-1 at 20˚C. Equilibrium studies showed that experimental data were well fitted to Langmuir–Freundlich isotherm model. Linear and non-linear forms of pseudo-first-order and pseudo-second-order kinetic models were employed to describe the kinetic adsorption processes. The model parameters were confidently recovered. The kinetics followed the non-linear form of pseudo-first-order model which represents adsorption of Fe(II) on chitosan takes place through a physical process. The examination of kinetic data also revealed that the adsorption rate was dominated by intra-particle diffusion mechanism.